GP277 Evaluation of a novel disposable oscillating positive expiratory pressure (OPEP) device in a cohort of children with cystic fibrosis. (June 2019) - Kevin, J O'Sullivan; Power, Valerie; McGrath, Deirdre; Dunne, Colum; O'Sullivan, Leonard; Linnane, Barry
Abstract : Objectives: To evaluate use of a novel disposable Oscillating Positive Expiratory Pressure (OPEP) device (SoloPep) by children with CF. Methods: A convenience sample of 36 participants, all current OPEP device users, was recruited from a paediatric CF service. For one month, participants replaced their current OPEP devices (typically used daily for up to 6 months) with the SoloPep device (daily disposable), and followed their existing OPEP regimen. Lung function was assessed on the day that use of the new device was adopted and following completion of the test period using the EasyOne Air Spirometer (NDD Medzintechnik AG, Switzerland). Lung Clearance Index (LCI) was assessed via multiple-breath nitrogen washout (Exhalyser D, Eco Medics, Switzerland). User experience of SoloPep was evaluated with a post-study questionnaire, rated on five-point Likert scales. All participants were trained at the first clinic visit to use the SoloPep device utilising a proprietary software program. Results: 31 participants completed the study: 13 females; median age 10 years, range 4–16 years. Lung function (mean ± SD;%FEV1, baseline = 83.26 ± 19.63, follow-up = 86.31 ± 20.95;%FVC, baseline = 92.65 ± 16.02, follow-up = 94.32 ± 16.82; FEV1 : FVC, baseline = 0.79 ± 0.11, follow-up = 0.80 ± 0.10) and LCI (mean ± SD; baseline = 10.05 ± 2.86, follow-up = 9.66 ± 2.10) were unchanged post-intervention. Most participants felt that SoloPep was easy to use (72% Strongly Agree; 24% Agree; 4% Neutral), addressed issues they had with cleaning their current OPEP device (72% Strongly Agree; 16% Agree; 12% Neutral), and encouraged them to perform their OPEP therapy more regularly (52% Strongly Agree; 28% Agree; 16% Neutral, 4% Strongly Disagree). All participants agreed that they would like to use SoloPep as their usual OPEP device (76% Strongly Agree; 24% Agree). No adverse device-related events were reported during SoloPep use. Conclusion: SoloPep was developed as a daily disposable OPEP device to reduce the risk of infection due to poor device cleaning. It is a convenient, user-friendly alternative to currently available OPEP devices. Over the course of the study, lung function was maintained, no adverse events were reported, and positive user experiences of the device were reported. Therefore, SoloPep may be a useful adjunct to aid airway clearance in children with CF.